Pseudomonas Aeruginosa Sepsis in a Previously Healthy Infant with Subcutaneous Nodules and Mastoid Bone Destruction - Azapağası, Ebru; Öz, Fatma Nur; Uysal Yazıcı, Mutlu; Ceylan, Dilara; Ocak, Emre; Taşçı Yıldız, Yasemin; Aytekin, Caner (Journal of Pediatric Intensive Care, 2020)
Pseudomonas aeruginosa septicemia is rare in previously healthy children. Skin lesions such as subcutaneous nodules and ecthyma gangrenosum may be the first manifestation of Pseudomonas infection that have rarely been reported. Herein we reported a previously healthy 6-month-old boy patient who presented with suppurative otitis media, multiple nodules, septic shock, and P. aeruginosa was identified in cultures of the blood, skin lesions, and purulent material of his ears.
Keywords: ecthyma gangrenosum; healthy infant; mastoid bone; Pseudomonas aeruginosa; subcutaneous nodules